2020
DOI: 10.20511/pyr2020.v8nspe2.795
|View full text |Cite
|
Sign up to set email alerts
|

Peacebuilding Strategies in Conflict Societies Through Art Education: Cyprus

Abstract: The purpose of this study is to include the evaluation of teacher opinions concerning the acquisition of peace culture by students through art education programs applied in Northern and Southern Cyprus. The study is patterned according to qualitative research method and is performed with focus group interview. The research included 10 secondary school (K12) 7th grade visual arts course teachers in total form both Northern Cypriot Turkish community (n=5) and Southern Cypriot Greek community (n=5). In the study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 10 publications
0
2
0
2
Order By: Relevance
“…It focuses on the role of art education in preserving cultural heritage, delving not only into skill transmission but also into historical traditions and cultural values [41]. Through keywords like "Cyprus" and "professional identity" [42], the theme examines the impact of geographical cultural uniqueness on art education and its influence on individual career development and identity formation. The theme emphasizes the significance of local culture in art education and its role in enhancing students' cultural identity awareness and sense of belonging [34].…”
Section: Research Theme 5: Art Education In Cultural Heritage and Ide...mentioning
confidence: 99%
“…It focuses on the role of art education in preserving cultural heritage, delving not only into skill transmission but also into historical traditions and cultural values [41]. Through keywords like "Cyprus" and "professional identity" [42], the theme examines the impact of geographical cultural uniqueness on art education and its influence on individual career development and identity formation. The theme emphasizes the significance of local culture in art education and its role in enhancing students' cultural identity awareness and sense of belonging [34].…”
Section: Research Theme 5: Art Education In Cultural Heritage and Ide...mentioning
confidence: 99%
“…Por otra parte, diez investigaciones (37%) se orientaron a conocer y evaluar cómo la cultura de paz se introduce en el currículo oficial y operacional (Acosta Oidor et al, 2021;Akudolu y Umenyi, 2016;Cots y Gálvez, 2016;Chiriswa y Thinguri, 2015;Miralay, 2020;Mishra et al, 2020;Mishra, 2021;Mustapha et al, 2016;Olowo, 2016;Zembylas y Loukaidis, 2021).…”
Section: La Inclusión De La Cultura De Paz En El Currículo Escolarunclassified
“…En cuanto a la inclusión de la paz en los planes de estudio, los participantes destacan la importancia de introdur la cultura de paz en los planes y en los contenidos de todos los cursos, reconociendo que esto permite fomentar la conciencia de paz entre los jóvenes, promover los derechos humanos, además de reducir los niveles de violencia (Miralay;2020;Olowo, 2016). En un primer lugar, se identificó que las asignaturas orientadas a lo social y las humanidades -como historia, educación cívica, artes, educación para la ciudadanía-, incluyen en sus objetivos y contenidos, mensajes de paz (Acosta Oidor et al, 2021;Chiriswa y Thinguri, 2015;Olowo, 2016).…”
Section: La Inclusión De La Cultura De Paz En El Currículo Escolarunclassified
“…In the teaching field, Miralay (2020) found that according to teachers' perceptions, the awareness of the culture of peace by students through arts education would promote individual and social peace. They also found that families, school administrators and governmental institutions have an essential role in promoting peace.…”
Section: Examples Of Peace-building Initiatives From Institutions Res...mentioning
confidence: 99%